2006
DOI: 10.1111/j.1365-2249.2006.03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein array autoantibody profiles for insights into systemic lupus erythematosus and incomplete lupus syndromes

Abstract: SummaryThe objective of this study was to investigate the prevalence and clinical significance of a spectrum of autoantibodies in systemic lupus erythematosus and incomplete lupus syndromes using a proteome microarray bearing 70 autoantigens. Microarrays containing candidate autoantigens or control proteins were printed on 16-section slides. These arrays were used to profile 93 serum samples from patients with systemic lupus erythematosus (SLE (n = 33), incomplete LE (ILE; n = 23), first-degree relatives (FDRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(198 citation statements)
references
References 29 publications
9
180
2
1
Order By: Relevance
“…Despite the decreased percentages and impaired in vitro-suppressive activity of their Tregs, Dock8 -/-mice aged for 12 months had normal weight gain and did not develop lymphadenopathy, splenomegaly, anemia, thrombocytopenia, or gastrointestinal inflammation. In addition, their sera did not exhibit increased reactivity to HEp-2 cell antigens or to the 128 autoantigens included in the University of Texas Southwestern panel (37) compared with WT controls (data not shown). Intraperitoneal administration of the TLR3 agonist poly(I:C) for 3 months to mimic microbial stimulation did not elicit autoantibody formation against HEp-2 cells and did not provoke autoimmune disease in Dock8 -/-mice (data not shown).…”
Section: Cd25mentioning
confidence: 93%
“…Despite the decreased percentages and impaired in vitro-suppressive activity of their Tregs, Dock8 -/-mice aged for 12 months had normal weight gain and did not develop lymphadenopathy, splenomegaly, anemia, thrombocytopenia, or gastrointestinal inflammation. In addition, their sera did not exhibit increased reactivity to HEp-2 cell antigens or to the 128 autoantigens included in the University of Texas Southwestern panel (37) compared with WT controls (data not shown). Intraperitoneal administration of the TLR3 agonist poly(I:C) for 3 months to mimic microbial stimulation did not elicit autoantibody formation against HEp-2 cells and did not provoke autoimmune disease in Dock8 -/-mice (data not shown).…”
Section: Cd25mentioning
confidence: 93%
“…10 Screening for a broad panel of IgM and IgG autoantibodies was performed with autoantibody arrays (University of Texas Southwestern Medical Center, Genomic and Microarray Core Facility) as described. 14 …”
Section: Immunizations and (Auto) Ab Detectionmentioning
confidence: 99%
“…In studies with a limited number of samples, investigators demonstrated that IgM autoantibodies predominated over IgG in patients with incomplete lupus erythematosus (at least 1 but less than 4 of the criteria for SLE (12 )). IgG usually predominates in SLE, however (13 ). It will be of interest to use NALIA arrays to evaluate this observation by detecting IgM and IgG autoantibodies separately rather than simultaneously, which was the approach we used.…”
Section: Discussionmentioning
confidence: 99%